Development of Augmented Reality Media using Gender-Based Tri Hita Karana to Facilitate Students' Liability towards Local Culture - Indrawan, I Putu Eka; Sutajaya, I Made; Suja, I Wayan (Jurnal Paedagogy, 2024)
This study aims to develop Augmented Reality (AR) media using Gender-based Tri Hita Karana to facilitate students' liability towards local culture. This study utilized the Research and Development (R&D) approach with 48 fifth-grade students at SD Negeri 11 Denpasar as subjects. The instruments used in this research were expert validation questionnaires and student questionnaires, while the data analysis techniques include Aiken's V index for expert validation and descriptive analysis of student responses. With an average score of 0.992, the expert validation results using Aiken's V index demonstrate that this augmented reality media was quite legitimate. Furthermore, the study of the student questionnaire reveals a favorable reaction towards the enjoyment of local culture, as indicated by an average score of 3.137. This study determined that combining augmented reality (AR) technology with cultural knowledge-based learning could be a novel approach in contemporary education.